EFFECTS OF RAMADAN FASTING ON BLOOD PRESSURE IN NORMOTENSIVE MALES - Samad, Fatima; Qazi, Fahd; Pervaiz, Mohammad B; Kella, Danesh K; Mansoor, Maryah; Osmani, Bushra Z; Mir, Fazia; Kadir, Muhammad Masood (Journal of Ayub Medical College Abbottabad, 2015)
Background: Research has been done to investigate the effect of intermittent complete fasting on human physiological parameters but the effect of fasting on blood pressure remains relatively unexplored. Research in animal models suggests a hypotensive effect with an undetermined mechanism. Muslims worldwide fast daily from dawn to dusk throughout the Islamic month of Ramadan. This study was to investigate the proposed hypotensive effect of Ramadan fasting in males over a period of 20 days and to study the relationship of the pattern of blood pressure variation with body mass index change. Methods: A repeated measures observational study design was implemented with convenient sampling. Study group included 40 normotensive, non-smoker males with no known comorbidities between the ages of 18-40 who fasted daily in the month of Ramadan. One set of BP readings, each, was taken one week before the start of Ramadan and on the 7th, 14th and 21st day of Ramadan which included pre and post Iftar measurements along with other variables. Data was analysed by repeated measures ANOVA using SPSS. The differences were compared with critical values generated by Tukey’s Method. Results: There was a significant drop in systolic BP of 7.61 mmHg before Iftar, 2.72mmHg after Iftar (p<0.005). There was a significant effect of Ramadan on diastolic BP (p<0.005), the drop being 3.19 mmHg. The drop in body mass index was significant only before Iftar at 0.3kg/m2 (p<0.005). Pulse rate showed a significant drop of 7.79 bpm before Iftar and a significant rise of 3.96 bpm (p<0.005). Conclusions: Intermittent fasting causes a drop in both systolic and diastolic blood pressure in normotensive males. Keywords: Ramdan, Iftar, Normotensive, Fasting, Body Mass Index